(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: According to world statistics, heart failure is one of the five leading causes of death, second after coronary artery disease and stroke. In parallel with the aging population, the proportion of elderly people with heart failure is increasing. Elderly heart failure patients have a worse prognosis than the younger with high rates of mortality and hospitalization. Comprehensive assessment of the elderly has been shown to improve both mortality and prolong life, especially in heart failure. Methods: A cross - sectional descriptive study on elderly patients diagnosed with stable heart failure with reduced ejection fraction at the Cardiology Department – Thong Nhat Hospital from November 2023 to May 2024. Results: The study was conducted on 44 elderly patients with an average age of 72.20 ± 8.8 years, male ratio was 59.1%. 100% polymorbidity patients, 100% patients with polypharmacy, 31.8% of patients reduced Basic Activities of Daily Living and 63.6% reduced Instrumental Activities of Daily Living. 61.3% of patients were frailty, 47.7% patients with declined in cognitive functions, 43.2% of patients had depressive disorder and 29.5% were malnourished. Conclusion: Comprehensive geriatric assessment helps early identification and comprehensive treatment in elderly patients, especially in heart failure patients who have a high rate of geriatric diseases.